С акцентом - моим …: стихи / Вячеслав Ар-Серги - Ар-Серги Вячеслав Витальевич (У Никитских ворот, 2021)
Экземпляры: (20220420) / Инвентарный номер: 63028 / Цена: 150.00 / Сис.шифр: Р2 / Авт.знак: С 32 / ГРНТИ: 17.82.10 / ББК: 84(2Рос=Рус)6